Experimental Studies of Compressive Strength of Sustainable Concrete with Partial Cement Substitution Using Palm Oil Boiler Ash - Suraedi, Daral; Sjah, Jessica; Handika, Nuraziz; Aulia, Saffanah Fasya; Edwardo, Karmenita Olivia (CSID Journal of Infrastructure Development, 2026)
This study investigates the mechanical performance of sustainable concrete incorporating Palm Oil Boiler Ash (POBA) as a partial cement replacement. As the construction sector seeks to reduce CO₂ emissions and manage agro-industrial waste, POBA emerges as a promising supplementary cementitious material due to its pozzolanic potential and abundance in palm oil–producing regions such as Indonesia.Concrete specimens were prepared with POBA substitution levels ranging from approximately 10% to 30% by weight of cement, in combination with nanosilica and a polycarboxylate ether (PCE) superplasticizer to enhance performance. The mix design was developed in accordance with ACI 211 guidelines to maintain comparable workability across all mixtures.Compressive strength was evaluated at 3, 14, 28, and 56 days. Results indicate that while early-age strength decreases with increasing POBA content, an optimal replacement level of 19% demonstrated compressive strength comparable to the control mixture at later ages under the tested mix design conditions. The inclusion of nanosilica, based on prior experimental validation, is considered to have contributed to mitigating early strength reduction and supporting microstructural development. The study concludes that POBA, when applied at an optimal replacement level, can serve as a viable partial cement substitute for structural concrete applications, supporting environmental sustainability and low-carbon infrastructure development.